The effects of the removal of electronic devices for 48 hours on sleep in elite judo athletes - Dunican, I. C.; Martin, D. T.; Halson, S. L.; Reale, R. J.; Dawson, B. T.; Caldwell, J. A.; Jones, M. J.; Eastwood, P. R. (The Journal of Strength and Conditioning Research, 2017)
This study examined the effects of evening use of electronic devices (i.e., smartphones, etc.) on sleep quality and next-day athletic and cognitive performance in elite judo athletes. Over 6 consecutive days and nights, 23 elite Australian judo athletes were monitored while attending a camp at the Australian Institute of Sport (AIS). In 14 athletes, all electronic devices were removed on days 3 and 4 (i.e., for 48 hours: the "device-restricted group"), whereas 9 were permitted to use their devices throughout the camp (the "control group"). All athletes wore an activity monitor (Readiband) continuously to provide measures of sleep quantity and quality. Other self-reported (diary) measures included time in bed, electronic device use, and rate of perceived exertion during training periods. Cognitive performance (Cogstate) and physical performance (single leg triple hop test) were also measured. When considering night 2 as a "baseline" for each group, removal of electronic devices on nights 3 and 4 (device-restricted group) resulted in no significant differences in any sleep-related measure between the groups. When comparing actigraphy-based measures of sleep to subjective measures, all athletes significantly overestimated sleep duration by 58 ± 85 minutes (p = 0.001) per night and underestimated time of sleep onset by 37 ± 72 minutes (p = 0.001) per night. No differences in physical or cognitive function were observed between the groups. Conclusion: This study has shown that the removal of electronic devices for a period of two nights (48 hours) during a judo camp does not affect sleep quality or quantity or influence athletic or cognitive performance.